Metal-nanoparticle-G4-DNA conjugates and their DC conductivity measurements - Parviainen, Teemu (2013)
Due to superior self-assembly properties, DNA is a very promising candidate for the basis of future bottom-up solutions for molecular electronics and therefore the conductivity of DNA is a very crucial question. In this work DC conductivity measurements on conjugates consisting of G-quadruplex DNA and metal nanoparticles were carried out. The fabrication and results obtained from the electrical measurements of three types of conjugates (20nm G4-AgNP chains, 20nm G4-AuNP flowers and 60nm G4-AuNPs) are reported. Additionally, 20nm AuNP chains coated with G4 were fabricated but not measured electrically. Results reported here indicate that in ambient conditions G4-DNA exhibits insulating behaviour with the resistance of the order of 1 TOhm. However, it was demonstrated that increasing the relative humidity affects to the intrinsic resistance of G4-DNA. The resistance of the conjugates was decreased down to 200 MOhm in the relative humidity of 80 %.